Role Of Heart Rate Response To Standing And Valsalva Manoeuvre Measurement In Diagnosing Cardiovascular Autonomic Neuropathy In Patients With Diabetes Mellitus. (Indian Journal of Applied-Basic Medical Sciences, 2020)
Diabetes is an iceberg disease with many complications like cardiovascular disease &diabetic  neuropathy. One of the most overlooked of all serious complications of diabetes is cardiovascular autonomic neuropathy (CAN), Autonomic nervous system dysfunction is one  of the significant complications of diabetes mellitus and this is generally associated with a  poor prognosis. Standard cardiovascular reflex tests are used to assess cardiovascular  autonomic function. These include changes in heart rate during standing up and, Valsalva  manoeuvre to assess cardiac parasympathetic activity. Aim: To analyse the role of heart  rate during standing up and , Valsalva manoeuvre in diagnosing Cardiac Autonomic  Neuropathy. Method: In this cross sectional study, 30 diabetics were compared with 30  non-diabetics (plasma glucose level between 80-120 mg %) for their autonomic functions.  Each subject was evaluated for cardiovascular autonomic neuropathy by heart rate during  standing up and , Valsalva manoeuvre Statistically analysis was performed using t test.  Results: There was statistically significant (p
Keywords: Diabetes mellitus; Autonomic neuropathy; Autonomic function tests